Training in Scientific Writing Based on Digital Tools to Achieve Publication in Reputable National Journals - Endah Kurniawati; Rike Kusuma Wardhani; Kukuh Harianto (Journal Of Humanities Community Empowerment, 2026)
Scientific publication frequently poses a crucial obstacle for students due to limited proficiency in literature mapping and identifying appropriate target journals. This community service activity aims to enhance students' competence in drafting scientific articles by integrating digital research tools. The scope of the program focuses on utilizing specialized software to identify high-quality references and formulating strategies to navigate reputable national journals indexed in Sinta 3. The participatory training was conducted through a synchronous online method using the Zoom Meeting platform. Through this activity, students acquired skills in operating mapping features within the Publish or Perish and Connected Papers applications to strengthen the theoretical foundations of their manuscripts. The implementation results demonstrate a significant improvement in students technical skills in scientific writing. In conclusion, the mastery of digital research tools effectively enhances the productivity and quality of students scientific outputs within the higher education environmen